Resilience Rural Banks Pasca Covid-19 - Puspitasari, Devy Mawarnie; Chin, Jacky; Dasman, Sunita; Indriani, Poppy; Saputro, Rizal Sigit (Universitas Dharma Wacana, 2024)
Beginning with a health crisis, the Covid-19 pandemic has had a domino effect on social, economic, and financial aspects. The economy has experienced a slowdown, accompanied by a decline in purchasing power due to reduced income. Tourist areas have become completely deserted, resulting in a lack of income and economic activity. The impact of the pandemic has inevitably spread to the banking sector, particularly affecting Rural Banks (known as BPR). The role of BPR, as part of the government's strategy for local economic development and labor absorption, has also been disrupted. In Indonesia, BPR has long been the backbone of microfinance, serving micro, small, and medium enterprises (MSMEs). However, the Covid-19 pandemic has shaken this sector, forcing BPRs to confront challenges while exploring new opportunities for resilience. This research recommends that Rural Banks strengthen risk management and operational efficiency to enhance their resilience in the future.This research contributes to the existing literature by providing a focused analysis of Rural Banks specific financial performance variables and recommends that Rural Banks strengthen risk management and operational efficiency to enhance their resilience in the future. The research employs logit analysis to develop a prediction model. The findings indicate that the resilience model can serve as a predictive tool for BPR resilience in the post-pandemic period, supporting economic empowerment, particularly for MSMEs and labor absorption. This study introduces the concept of Off-Balance Sheet management as a strategic tool for enhancing resilience, which has been underexplored in the context of rural banking in Indonesia.